2019
DOI: 10.1109/tuffc.2018.2881409
|View full text |Cite
|
Sign up to set email alerts
|

An FPGA-Based Backend System for Intravascular Photoacoustic and Ultrasound Imaging

Abstract: The integration of intravascular ultrasound (IVUS) and intravascular photoacoustic (IVPA) imaging produces an imaging modality with high sensitivity and specificity which is particularly needed in interventional cardiology. Conventional side-looking IVUS imaging with a single-element ultrasound (US) transducer lacks forward-viewing capability, which limits the application of this imaging mode in intravascular intervention guidance, Doppler-based flow measurement, and visualization of nearly or totally blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…For the space-constrained TRUSPA imaging, a curvilinear ultrasound array consisting of 128 or 196 elements is desired to generate prostate images with higher quality and a wider field-of-view, for example in conventional TRUS prostate imaging. Although this and previous studies demonstrated the high PA sensitivity of CMUTs [ 26 , 27 ], the unavailability of curvilinear CMUT arrays limit their use for developing a wide field-of-view clinical-grade TRUSPA device. This limitation also extends for emerging piezoelectric micromachined ultrasound transducer (PMUT) arrays, which recently showed good experimental results for deep-tissue photoacoustic imaging applications [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 81%
“…For the space-constrained TRUSPA imaging, a curvilinear ultrasound array consisting of 128 or 196 elements is desired to generate prostate images with higher quality and a wider field-of-view, for example in conventional TRUS prostate imaging. Although this and previous studies demonstrated the high PA sensitivity of CMUTs [ 26 , 27 ], the unavailability of curvilinear CMUT arrays limit their use for developing a wide field-of-view clinical-grade TRUSPA device. This limitation also extends for emerging piezoelectric micromachined ultrasound transducer (PMUT) arrays, which recently showed good experimental results for deep-tissue photoacoustic imaging applications [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 81%
“…Its design and investigation are of great significance. Vacuum CMUT can be widely used in many fields such as intravascular ultrasound detection [ 11 ], intravascular photoacoustic imaging [ 12 ], tissue harmonic imaging [ 13 ], high-intensity focused ultrasound therapy [ 14 ], and liquid flow velocity measurement [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an acoustic–electric conversion element, the CMUT’s working efficiency is characterized by its performance parameters such as transmission sound pressure, reception sensitivity, and fractional bandwidth [ 12 ]. In the design process, it is necessary to optimize the structural parameters that affect these performances to improve the efficiency of the CMUT.…”
Section: Introductionmentioning
confidence: 99%
“…It also needs to be mentioned that FPGA can now support efficient backend processing for US imaging or PA imaging in a configurable and convenient way [113].…”
Section: Photoacoustic Sensor For In Vivo Imagingmentioning
confidence: 99%
“…20 (a) demonstrates the PA/US system's schematic where the FPGA is used to control the laser, and the imaging process is achieved by the FPGA backend, where the system is implemented in the register-transfer level. The FPGA, ADC board, and CMU sensing front-end used in the system are demonstrated in Fig.2.20(b)[113].…”
mentioning
confidence: 99%